2009
DOI: 10.1152/ajpregu.90783.2008
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon induces the gene expression of aquaporin-8 but not that of aquaporin-9 water channels in the rat hepatocyte

Abstract: Glucagon stimulates the vesicle trafficking of aquaporin-8 (AQP8) water channels to the rat hepatocyte canalicular membranes, a process thought to be relevant to glucagon-induced bile secretion. In this study, we investigated whether glucagon is able to modulate the gene expression of hepatocyte AQP8. Glucagon was administered to rats at 0.2 mg/100 g body wt ip in 2, 3, or 6 equally spaced doses for 8, 16, and 36 h, respectively. Immunoblotting analysis showed that hepatic 34-kDa AQP8 was significantly increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 57 publications
1
20
0
Order By: Relevance
“…It has been reported that H-89 inhibits Akt, ROCK II, and 5'-AMP-activated protein kinase (AMPK) [35] and that the PKA pathway interacts with the PI3K/Akt pathway in the regulation of gene expression [36] . Previous studies have shown that the forskolin-induced stimulation of PKA can inhibit Akt activity in human embryonic kidney cells [37] , but epinephrine or forskolin-induced stimulation of PKA enhanced eNOS phosphorylation at Ser 1177 by activating the Akt pathway in aortic or coronary endothelial cells [28,38] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that H-89 inhibits Akt, ROCK II, and 5'-AMP-activated protein kinase (AMPK) [35] and that the PKA pathway interacts with the PI3K/Akt pathway in the regulation of gene expression [36] . Previous studies have shown that the forskolin-induced stimulation of PKA can inhibit Akt activity in human embryonic kidney cells [37] , but epinephrine or forskolin-induced stimulation of PKA enhanced eNOS phosphorylation at Ser 1177 by activating the Akt pathway in aortic or coronary endothelial cells [28,38] .…”
Section: Discussionmentioning
confidence: 99%
“…However, because no AU-rich elements are present in the mRNA 3=-untranslated region of AQP8, mechanisms of upregulation other than mRNA stabilization seem to be taking place. In our laboratory, we have described that glucagon promoted a decrease in calpain-mediated AQP8 proteolysis in rat hepatocytes (41). During metabolic acidosis, the decreased expression of other proteases (e.g., cathepsin B) may contribute to the decreased rate of protein turnover (9).…”
Section: Discussionmentioning
confidence: 99%
“…In the cases of embryos, larvae, oocyte and kidney, aquaporins were artificially expressed on the cellular membrane prior to cryopreservation. Contrastingly, in the current investigation, the fact that aquaporins can be increased in the cellular membrane by the translocation of AQP8 from the intracellular vesicles under the influence of choleretic stimuli such as dibutyryl cAMP (Bt2cAMP) [6] and glucagon [8,9,20], was utilized. As such, it was verified by the confocal immunofluorescence which showed increased AQP8 localization at the cellular boundaries on treatment with Bt 2 cAMP or glucagon.…”
Section: Discussionmentioning
confidence: 99%
“…Literature suggests that the longer the cells are treated with glucagon, the more AQP8 translocates to the cellular membrane. Results from Soria et al [20] suggested that treatment of hepatocytes with glucagon for 36 h showed an 120% increase in the quantity of AQP8 on cellular membrane as opposed to 80% increase for a 16 h treatment. On the contrary, for Bt 2 cAMP, some researchers indicate 10 min incubation is enough for effective translocation of AQP8 [11] whereas others recommend 12 h [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation